(untitled) (Research in Agriculture Livestock and Fisheries, 2018)
The research work was conducted at the Artificial Insemination Center under the Department of Animal Breeding and Genetics, Bangladesh Agricultural University, Mymensingh to compare the efficacy between Egg Yolk Citrate (EYC) and Tris diluter for frozen semen production in Black Bengal buck. The parameters of semen characteristics included volume per ejaculate (ml), percentage of individual motility (progressive), normal and live sperm and sperm concentration (billion/ml). After dilution with EYC extender, It revealed from statistical analysis of frozen semen that individual bucks had significant effect (p<0.05) on sperm motility and but insignificant on motility after cooling with and without glycerol. In the same way, with Tris diluter, it was insignificant (p>0.05) on diluted semen motility and motility after cooling with and without glycerol. Motility and morphology of the sperm after equilibration and thawing showed insignificant difference among the bucks using EYC diluter. On the contrary, variation in the motility after equilibration and thawing was found significant (p<0.05) using Tris diluter and insignificant on normal and live sperm percentages. After insemination with frozen buck semen, productivity or conception rate was found significantly (p<0.01) higher (60.37%) in Tris than that of EYC diluter (43.75%). On the other hand, the productivity when compared among bucks within the diluter, the variation was not found significant (p>0.05).The productivity found both in Tris and EYC diluter is almost similar to abundantly used Triladyl diluter (58.25). It is concluded that tris diluter might be used as the alternative to the Tryladil diluter though further study is to be needed for more confirmation. Res. Agric., Livest. Fish.5(3): 341-350, December 2018